Telomere length is an independent prognostic marker in MDS but not in de novo AML. (9th May 2017) - Williams, Jenna; Heppel, Nicole H.; Britt‐Compton, Bethan; Grimstead, Julia W.; Jones, Rhiannon E.; Tauro, Sudhir; Bowen, David T.; Knapper, Steven; Groves, Michael; Hills, Robert K.; Pepper, Chris; Baird, Duncan M.; et al.
Summary: Telomere dysfunction is implicated in the generation of large‐scale genomic rearrangements that drive progression to malignancy. In this study we used high‐resolution single telomere length analysis (STELA) to examine the potential role of telomere dysfunction in 80 myelodysplastic syndrome (MDS) and 95 de novo acute myeloid leukaemia (AML) patients. Despite the MDS cohort being older, they had significantly longer telomeres than the AML cohort ( P  < 0·0001) where telomere length was also significantly shorter in younger AML patients (age <60 years) ( P  = 0·02) and in FLT3 internal tandem duplication‐mutated AML patients ( P  = 0·03). Using a previously determined telomere length threshold for telomere dysfunction (3·81 kb) did not provide prognostic resolution in AML [Hazard ratio (HR) = 0·68, P  = 0·2]. In contrast, the same length threshold was highly prognostic for overall survival in the MDS cohort (HR = 5·0, P  < 0·0001). Furthermore, this telomere length threshold was an independent parameter in multivariate analysis when adjusted for age, gender, cytogenetic risk group, number of cytopenias and International Prognostic Scoring System (IPSS) score (HR = 2·27, P  < 0·0001). Therefore, telomere length should be assessed in a larger prospective study to confirm its prognostic role in MDS with a view to integrating this variable into a revised IPSS.